Fate of ejected debris from the explosion of the rear surface of fused silica in the high-power laser facility - Ge Peng; Qiang Gao; Lingxi Liang; Zhe Dong; Jiaxuan Chen; Chengyu Zhu; Peng Zhang; Lihua Lu (International Journal of Optomechatronics, 2023)
AbstractThis study focuses on the issue of uncontrollable debris generated by laser-matter interactions in high-power laser facilities, which significantly impairs operational efficiency. The maximum motion distance of debris, referred to as the safety distance, is a crucial parameter that this work investigates. Three prediction methods that utilize aerodynamic coefficients and trajectories are proposed, with input parameters derived from velocity curves extracted from high-resolution time-resolved images. The results obtained from these methods show good agreement with experimental data collected under laser fluence conditions ranging from 18 to 79 J/cm2 that damage the rear surface of fused silica. The analytically predicted safety distance, with an input velocity fitted at 0 ns and an upper diameter limit of 10 µm, was closest to the experimental result at 155 mm. Analytically predicted values with input velocities fitted at 13,000 ns and all diameter ranges did not exceed 192.3 mm. Numerically predicted values, with input velocity fitted at 13,000 ns and a median diameter of small debris (5 µm), were 140.4 and 295.2 mm for aspect ratios of 2 and 4, respectively. The numerical method is recommended for predicting the safety distance in high-power laser facilities, but obtaining accurate estimates of transient velocity is crucial for the method’s effectiveness.